2022
DOI: 10.1108/ijesm-08-2022-0013
|View full text |Cite
|
Sign up to set email alerts
|

CO2 emissions policy thresholds for renewable energy consumption on economic growth in OPEC member countries

Abstract: Purpose This study aims to examine the nexuses between economic growth, trade openness, renewable energy consumption and environmental degradation among organization of petroleum exporting countries (OPEC) members over the period 1990–2019. Design/methodology/approach The empirical strategy for the study includes dynamic heterogeneous panel pooled mean group (PMG), mean group (MG) estimators and dynamic panel threshold regression (TR) analysis. For clarity, PMG and MG are used to explore the long-run relatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(4 citation statements)
references
References 63 publications
0
4
0
Order By: Relevance
“…Similar findings can also be confirmed by for Vietnam. Abdulqadir (2021Abdulqadir ( , 2022Abdulqadir ( , 2023 recently examined various issues regarding the relationship between urbanization, renewable energy, and carbon dioxide emissions in sub-Saharan Africa. The author concluded that strong evidence of the Kuznets curve exists in the nexus between urbanization, economic growth, and renewable energy in these countries.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Similar findings can also be confirmed by for Vietnam. Abdulqadir (2021Abdulqadir ( , 2022Abdulqadir ( , 2023 recently examined various issues regarding the relationship between urbanization, renewable energy, and carbon dioxide emissions in sub-Saharan Africa. The author concluded that strong evidence of the Kuznets curve exists in the nexus between urbanization, economic growth, and renewable energy in these countries.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Senarathne and Jayasinghe (2021) conducted a study on some selected European and American countries over the period 1971–2014 and discovered a long-run impact of energy consumption on CO 2 emissions. Abdulqadir (2022a) found overwhelming evidence of an infliction point between CO 2 emissions metric tons per capita and renewable energy consumption in OPEC member countries over the period 1990–2019. In other studies, Abdulqadir (2022c) focused on the G7 countries, while Abdulqadir (2022b) focused on the MINT and BRICS countries.…”
Section: Brief Literature Reviewmentioning
confidence: 99%
“…Such an examination has often been carried out using some methodologies from the field of both applied mathematics and microeconomics. For example, an investigation by Abdulqadir [4] scrutinized the correlation between economic growth and environmental degradation among OPEC member nations via the pool mean group (PMG) technique. Analytical instruments such as panel co-integration assessments, dynamic OLS (DOLS), and the fully modified OLS (FMOLS) method offer valuable insights into fiscal expansion.…”
Section: Introductionmentioning
confidence: 99%